Representing the Problem of (Un)Ethical Practices in Canada’s Post-Pandemic International Student Policy Landscape - Harden-Wolfson, Emma; Hutcheson, Shannon; Zhang, Yvonne (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2025)
This study investigates how the Canadian policy landscape toward international students has changed since the pandemic. It uses a policy mapping of 97 announcements made between January of 2022 and March of 2024 by the federal government, the governments of Ontario and Quebec, and three organizations with expertise in international or higher education. Using the “What’s the problem represented to be?” (WPR) approach, the article analyses the increasing attention being paid to (un)ethical practices as a lens through which policy bodies are constructing the role of international students in Canada. This highlights the differing representations of the “problem” of ethical practices, as well as the call-and-response nature of announcements between policy actors. The focus on ethical practices has created links between international students and national issues such as housing shortages and labour market needs, assigning responsibility to unscrupulous actors but also to students themselves for creating these challenges.